2018
DOI: 10.1111/ppa.12892
|View full text |Cite
|
Sign up to set email alerts
|

Serological, molecular and immunofluorescent evidence for interference competition between isolates of Potato virus Y

Abstract: Under natural field conditions, the abundance of plant viruses sharing the same host frequently results in mixed infections. Viruses co‐occurring inside host tissues often interact with one another synergistically or antagonistically. This paper addresses within‐host interactions among genetically different isolates of Potato virus Y (PVY), a serious pathogen that attacks solanaceous crops, particularly potato and tobacco. Manifold aspects of the relationships between six PVY isolates representing PVYO, PVYN‐W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
(62 reference statements)
0
7
0
1
Order By: Relevance
“…Several reports of PVY interactions in mixed infections have been previously published, showing an antagonistic nature, depending on the viral strains [13,47], and even partial cross-protection [48]. It was shown that PVY-NTN superinfection decreased the titers of PVY-N:O and PVY-N-Wi, while existing PVY-NTN infection prevented infection by secondary virus in some cases, while its titer was unaffected by PVY-N:O, PVY-N-Wi, or PVY-O [48]. Such information could be useful to discriminate between potential strain mixtures as in the case reported here, although it would be impossible to determine the time of infection by individual strains.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of PVY interactions in mixed infections have been previously published, showing an antagonistic nature, depending on the viral strains [13,47], and even partial cross-protection [48]. It was shown that PVY-NTN superinfection decreased the titers of PVY-N:O and PVY-N-Wi, while existing PVY-NTN infection prevented infection by secondary virus in some cases, while its titer was unaffected by PVY-N:O, PVY-N-Wi, or PVY-O [48]. Such information could be useful to discriminate between potential strain mixtures as in the case reported here, although it would be impossible to determine the time of infection by individual strains.…”
Section: Discussionmentioning
confidence: 99%
“…To double-check the potato cultivars, all analysed potato plants were tested for the presence of PVY using ELISA [ 52 ]. ELISA testing was performed according to [ 53 ], and the results are presented in Table S1 . Absorbance was measured at 405 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Grupa et al . [78] reported that two different strains of PVY rarely occupied the same cells of infected potato at 21 to 35 days p.i. In another previous study Dietrich and Maiss [40] found that co-infections of differently labelled strains of three potyviruses remained spatially separated with the exception of a few cells at the infection interface, whereas co-infections of any of the potyviruses with potato virus X led to a preponderance of co-infected cells.…”
Section: Discussionmentioning
confidence: 99%